2013
DOI: 10.1097/mao.0b013e318298dedc
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Contralateral Hearing Loss After 2 Craniotomies for Vestibular Schwannoma

Abstract: The recurrence of contralateral hearing loss after craniotomies years apart suggests that patient specific anatomic risk factors predispose an individual to hearing loss after contralateral cerebellopontine angle surgery. Patients with previous history of contralateral hearing loss should be counseled that they may be at increased risk for recurrent loss in the setting of re-resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The majority of patients had received steroids for their hearing loss treatment. 1 , 3 - 7 , 20 , 22 - 24 , 27 , 29 We found that hearing thresholds have been improved (partially or completely) in a significant number of these studies.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The majority of patients had received steroids for their hearing loss treatment. 1 , 3 - 7 , 20 , 22 - 24 , 27 , 29 We found that hearing thresholds have been improved (partially or completely) in a significant number of these studies.…”
Section: Resultsmentioning
confidence: 82%
“…Cerebrospinal fluid leakage was the most reported etiology in these studies. 1 , 4 , 9 , 20 , 24 , 26 - 28 , 30 Vascular decompression and sacrification of veins during the surgery and allergic responses have also been reported as a probable etiology of CoHL in these patients. The onset of hearing loss varied from immediately to 18 months after surgery.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It has also been shown that patients with anatomical features of cochlear aqueduct hyperpatent are at risk for contralateral hearing loss [9]. An enlarged CSF connection to the perilymphatic space may make the cochlea vulnerable to low-pressure transients, which following posterior fossa surgery, this condition may become recurrent [10]. However, there is no preoperative assessment for patency of the cochlear aqueduct [4].…”
Section: Discussionmentioning
confidence: 99%
“…Contralateral sudden sensorineural hearing loss (SNHL) occurring after cerebellopontine surgery is rare [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Presentation of petroclival meningioma followed by contralateral SNHL as a result of cerebellopontine surgery is quite uncommon, with only one case being previously reported [17].…”
Section: Introductionmentioning
confidence: 99%